2018
DOI: 10.1093/asj/sjy255
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study of the Chinese Nasal Keystone Region

Abstract: Background The keystone region is an important anatomical structure to consider in rhinoseptoplasty, because there are few published data regarding the keystone region in Chinese noses. Objectives The authors sought to describe the anatomy of the Chinese nasal keystone region and provide useful knowledge for rhinoseptoplasty. Methods Sixteen cadaveric heads (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In Asian reports, the cephalocaudal length of the overlapping area between the upper lateral cartilage and the nasal bone was 7 mm (range, 4-10 mm) in the midline, and 3.1 mm (range, 0-7 mm) in the paramedian area in a study by Kim et al [37] involving the dissection of 18 Korean cadavers. Han et al [38] reported that the nasal bone-upper lateral cartilage overlap was 6.47 ± 2.50 mm in the midline, 3.53 ± 2.23 mm on the left side, and 3.81 ± 2.56 mm on the right side in a study of 16 Chinese cadavers. In summary, the length of overlap between the nasal bone and cartilaginous septum tends to be shorter in Asians according to previous research.…”
Section: Keystone Areamentioning
confidence: 98%
See 1 more Smart Citation
“…In Asian reports, the cephalocaudal length of the overlapping area between the upper lateral cartilage and the nasal bone was 7 mm (range, 4-10 mm) in the midline, and 3.1 mm (range, 0-7 mm) in the paramedian area in a study by Kim et al [37] involving the dissection of 18 Korean cadavers. Han et al [38] reported that the nasal bone-upper lateral cartilage overlap was 6.47 ± 2.50 mm in the midline, 3.53 ± 2.23 mm on the left side, and 3.81 ± 2.56 mm on the right side in a study of 16 Chinese cadavers. In summary, the length of overlap between the nasal bone and cartilaginous septum tends to be shorter in Asians according to previous research.…”
Section: Keystone Areamentioning
confidence: 98%
“…16). In particular, the cartilage beneath the keystone area should be maximally preserved to maintain the stability of septal support and to prevent complications such as saddle nose deformity [38]. According to Mau et al [49], a wider L-strut and a greater extent of overlap in the junction at the keystone will improve stability against tensile stress.…”
Section: Septummentioning
confidence: 99%